Community intervention program: “The other face of caring” - Gonçalves, Mafalda Ferreira (2019)
Introduction: The informal caregiver (IC) provides assistance to disabled people without any financial gratification. Many stress factors are associated with the task of taking care of others, leading to physical and emotional deterioration. Studies indicate that approaches involving physical activity have a positive impact on the reduction of depression, stress, anger and overload presented by the IC. Objective: To reduce IC overload with a view to enabling the task of caring by acquiring tools for overload management. Methods: The data collection of ICs overload was made using Zarit scale from a previous database of 90 patients classified as “dementia” and 50 as “mental retardation”. 13 IC’s express their interest to be part of the project. The intervention consisted in health education sessions; yoga classes; establishment of a support group. The participant’s degree of overload and their satisfaction were assessed. Results: IC were mainly women (92%), with average age of 62 years. All scheduled sessions took place, with 23% participants withdrawing. Moderate to severe or severe overload level reduced from 92.3% to 60% at the end of the intervention and all participants classified the project as “good” or “very good”. Discussion: The project fulfilled the initial planning. Decrease of the IC overload was noted as evidenced in other studies. The limitation is the difficulty of IC in performing other activities besides then taking care of its dependent. Conclusions: The intervention had a positive impact in the ICs and the main goals were achieved. The health team continued this project through a partnership with a local social solidarity cooperative.